The characteristic of patulous eustachian tube patients diagnosed by the JOS diagnostic criteria. - Yoshinobu Kawamura; Ryoukichi Ikeda; Toshiaki Kikuchi; Hiromitsu Miyazaki; Tetsuaki Kawase; Yukio Katori; Toshimitsu Kobayashi (PLoS ONE, 2019)
Objective The objective is to describe characteristics of patients diagnosed with patulous Eustachian tube (PET) using the Diagnostic Criteria proposed by Japan Otological Society, and to evaluate the efficiency of objective tests to determine patent Eustachian tube. Study design Retrospective. Setting Tertiary referral center. Subjects A retrospective survey of medical records in Sen-En Rifu Hospital identified 78 ears of 56 patients with "Definite PET" diagnosed by the JOS Diagnostic Criteria between January 2017 and December 2017. Method Initial diagnosis, aural symptoms (voice autophony, aural fullness and breathing autophony), tubal obstruction procedures (posture change and pharyngeal orifice obstruction) and objective findings (tympanic membrane movement, Tubo-Tympano-Aerodynamic Graphy (TTAG) and sonotubometry) were evaluated. In addition, sonotubometry with postural change (Ohta's method), sitting CT and a newly devised PHI-10 score were also examined. Results Voice autophony, aural fullness, and breathing autophony were observed in 93.6%, 87.2%, 78.2%, respectively. In 91% of the ears, PET symptoms improved by postural change from sitting to the lying / forward-bending position. Synchronous movement of the TM upon respiration was observed in 69.1% of the ears. Positive findings of TTAG were observed in 75.6% of ears. Positive findings of sonotubometry were found in 55.1% of ears. Sonotubometry with postural change (Ohta's method), when the cut-off value of over 10dB was used, was positive in 45.2% of ears. Newly devised PHI-10 score representing severity of subjective symptoms classifying patients into no handicap, mild handicap, moderate handicap and severe handicap were observed in 12.2%, 10.8%, 18.9% and 58.1% of ears, respectively. The evaluation of the extent of patency of the ET by sitting CT indicated completely open, closed-short, and closed-long, in 68.6%, 11.4% and 21.4% of ears, respectively. Compared to the closed group, the completely open group had a significantly higher frequency of positive breathing autophony, positive sonotubometry, and positive Ohta's method. Conclusion The characteristics of main symptoms and the efficiency of various tests in PET diagnosis were analyzed based on data obtained from "Definite PET" patients diagnosed by the JOS Diagnostic Criteria. The greater the availability of tests to evaluate PET, the greater the opportunities to diagnose "Definite PET". In particular, tests measuring pressure transmission between the nasopharynx and middle ear, such as TM observation and TTAG, are more sensitive than sonotubometry measuring sound transmission.